Pengaruh Kompetensi Sdm Dan Disiplin Kerja Terhadap Kualitas Kinerja Pegawai Yang di Mediasi Oleh Pelayanan Publik: Studi Pada Dinas Perhubungan Kota Surbaya - Ali Mohamad Noor; Dhea Wahyuni; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
The Effect of HR Competence and Work Discipline on Employee Performance mediated by Public Service Quality (Study at the Surbaya City Transportation Office), Postgraduate Program, Wijaya Putra University. This type of research is explanatory, namely research that tests hypotheses between hypothesized variables to be tested. using a quantitative approach, the research sample was 95 respondents. In this study the data will be processed using SEM-PLS data analysis. The objectives of this study are: 1) To test and analyze the direct effect of HR competence on employee performance. 2) To test and analyze the direct effect of HR competencies on the quality of public services. 3) To test and analyze the direct effect of work discipline on employee performance. 4) To test and analyze the direct effect of work discipline on the quality of public services. 5) To test and analyze the direct effect of public service quality on employee performance. 6) To test and analyze the indirect effect of HR competencies on employee performance mediated by the quality of public services. 7) To test and analyze the indirect effect of work discipline on employee performance mediated by public service quality. The results showed that: 1) HR competence has a positive and insignificant effect on employee performance. This is evidenced by the original sample value of 0.597 and p-values of 0.179. 2) HR competence has a positive and significant effect on the quality of public services. This is evidenced by the original sample value of 0.223 and p-values of 0.000. 3) Work discipline has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.279 and p-values of 0.025. 4) Work discipline has a positive and insignificant effect on the quality of public services. This is evidenced by the original sample value of 0.198 and p-values of 0.263. 5) Public service quality has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.512 and p-values of 0.000. 6) HR competence has a significant positive effect on employee performance mediated by the quality of public services. This is evidenced by the original sample value of 0.305 and p-values of 0.009. 7) Work discipline has a significant positive effect on employee performance mediated by the quality of public services. This is evidenced by the original sample value of 0.143 and p-values of 0.038.